Targeted Promoter Replacement Reveals That Herpes Simplex Virus Type-1 and 2 Specific VP16 Promoters Direct Distinct Rates of Entry Into the Lytic Program in Sensory Neurons in vivo - Thompson, Richard L.; Sawtell, Nancy M. (Frontiers in Microbiology, 2019)
Infection and life-long residence in the human nervous system is central to herpes simplex virus (HSV) pathogenesis. Access is gained through innervating axonal projections of sensory neurons. This distinct mode of entry separates the viral genome from tegument proteins, including the potent transactivator of viral IE genes, VP16. This, in turn promotes a balance between lytic and latent infection which underlies the ability of the virus to invade, disseminate, and set-up a large reservoir of latent infections. In the mouse ocular model, TG neurons marked as either “latent” or “lytic” at 48 hrs post-infection indicated that these programs were selected early and were considered distinct and mutually exclusive. More recently, a temporal analysis of viral program selection revealed a default latent-like state that begins at ~18 hrs post-infection and in individual neurons, precedes entry into the viral lytic-cycle. Studies using refined viral mutants demonstrated that transition out of this latent program depended upon the transactivation function of VP16. Pursuit of the apparent incongruity between the established leaky-late-kinetics of VP16 expression with a “preimmediate-early” function led to the discovery of an unrecognized regulatory feature of the HSV-1 VP16 promoter near/downstream of its TATA box. Among three potential sites identified was a putative Egr-1/Sp1 site. Here we report that a refined mutation of this site, while having no impact on replication in cultured cells or cornea, resulted in ~100-fold reduction in lytic infection in TG in vivo. Notably, the HSV-2 VP16 promoter has thirteen direct tandem-repeats upstream of its TATA box forming multiple potential overlapping Egr-1/Sp1 sites. Thus, despite different structures, these promoters might share function in directing the preimmediate-early VP16 protein expression. To test this, the HSV-1 VP16 promoter/5’UTR was replaced by the HSV-2 VP16 promoter/5’UTR in the HSV-1 backbone. Compared to the genomically-repaired isolate, the HSV-2 VP16 promoter/5’UTR (i) accelerated the transition into the lytic cycle, and enhanced (ii) virulence, and (iii) entry into the lytic cycle following a reactivation stressor. These gain-of-function phenotypes support the hypothesis that the VP16 promoter regulates the latent/lytic boundary in neurons and that the HSV-1 and HSV-2 promoter/5’UTRs encode distinct thresholds for this transition.